2012
DOI: 10.1155/2012/483417
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Colorectal Cancer Screening Participation

Abstract: Colorectal cancer (CRC) is a major health problem worldwide. Although population-based CRC screening is strongly recommended in average-risk population, compliance rates are still far from the desirable rates. High levels of screening uptake are necessary for the success of any screening program. Therefore, the investigation of factors influencing participation is crucial prior to design and launches a population-based organized screening campaign. Several studies have identified screening behaviour factors re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
84
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 90 publications
8
84
2
2
Order By: Relevance
“…In our work, these factors include having a poor perception of health status, frequently visiting a physician, having one or more chronic diseases or having a mental illness. These are positively and notably associated in our study and in the majority of works published by other authors (Sewitch et al, 2007;Beydoun and Beydoun, 2008;Senore et al, 2010;Stock and Brenner, 2010;Gimeno-García et al, 2011;Gimeno-García, 2012;Carrasco-Garrido et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our work, these factors include having a poor perception of health status, frequently visiting a physician, having one or more chronic diseases or having a mental illness. These are positively and notably associated in our study and in the majority of works published by other authors (Sewitch et al, 2007;Beydoun and Beydoun, 2008;Senore et al, 2010;Stock and Brenner, 2010;Gimeno-García et al, 2011;Gimeno-García, 2012;Carrasco-Garrido et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…The lack of medical recommendations is one of the main obstacles revealed in other studies (Gimeno-García et al, 2011;Gimeno-García, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, age, gender and education level were reported to have no association with CRC screening when psychosocial factors were also included for examination in three reviews (Gimeno-García, 2012;Guessous et al, 2010;Power et al, 2009) and local studies (Leung et al, 2012b;So et al, 2012;Sung et al, 2008). In addition, the insignificant results of household income and having a chronic disease were consistent with previous local studies (So et al, 2012;Sung et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, in a recent study among Greek medical students it was shown that there is lack of information about CRC screening [16] . Awareness of the risk factors for CRC, signs and symptoms as well as the prognosis of the disease are all factors that can increase screening uptake [17,18] . European studies have reported low awareness about CRC compared to other cancers such as lung cancer and prostate in men and breast cancer in women [19] .…”
Section: Discussionmentioning
confidence: 99%
“…European studies have reported low awareness about CRC compared to other cancers such as lung cancer and prostate in men and breast cancer in women [19] . Low educational level has been associated with low participation rates in CRC screening programs [17] , whereas it has also been demonstrated that there is a positive association between low socio-economic status with low screening compliance rates [20] . Interestingly, the majority (55%) of employees who initially consent to be screened were at the intermediate of basic educational level (four nurses and 28 administrative/technical staff members) compared to those with high educational level (18 physicians, 4 nurses and 5 administrative/technical staff members).…”
Section: Discussionmentioning
confidence: 99%